Comparative Ergot Alkaloid Elaboration by Selected Plectenchymatic Mycelia of Claviceps purpurea through Sequential Cycles of Axenic Culture and Plant Parasitism - Peter Mantle (Biology, 2020)
Ergot alkaloids have an established place in plant pathology and toxicology. As pharmaceuticals, their sourcing is via natural or managed agricultural occurrence of sclerotia of Claviceps purpurea (Fr.) Tul. or through industrial fermentation processes with other Claviceps. The key factor for biosynthesis is differentiation of a particular mycelial anatomy. Previous study of these fungi from two disparate English grass genera, Spartina and Phragmites, has shown that only mycelia expressing a plectenchymatic sclerotium-like anatomy in specific axenic culture conditions elaborated ergot alkaloids, and then only as far as lysergic acid. The present report describes sequential cycles of axenic and parasitic cultivation for wild isolates from Dactylis and Alopecurus with intervention of a single ascospore step. This confirms the homozygous character of C. purpurea and defines several potential experimental axenic and parasitic conditions within the species for comparing genomic aspects of partial or full biosynthesis of cyclic tri-peptide alkaloids. Whereas Alopecurus ergot isolates readily parasitized rye, use of Dactylis isolates as inoculum for rye ovaries failed to cause the usual sphacelial fructification but supported growth of exceptionally thin sclerotia, sometimes two in a floret, with low alkaloid content attributed to reduced medullary component. However, after two cycles of axenic and rye-parasitic cultivation, and consistent re-selection of the plectenchymatic character in axenic mycelia, typical growth of ergot sclerotia occurred on rye. Caution thus seems necessary in tests for putative host specificity in any taxonomic realignments within the classical concept of C. purpurea. A Dactylis ergot isolate was also uniquely shown to parasitise the plumule of germinating rye seeds confirming the susceptibility of apical tissues. A key biosynthetic feature of a mycelial glyceride oil, rich in ricinoleic acid, as a prelude to axenic and parasitic formation of ergot alkaloids by C. purpurea is emphasised.